The Effect of Comprehensive Sexual Models on Self-Efficacy of Prevention of Sexual Violence in Adolescents at SMAN X Suwawa - Anindya Prananda Ishak; Nurdiana Djamaluddin; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2026)
Adolescents are an age group that is vulnerable to sexual violence due to limited knowledge and ability to protect themselves. Self-efficacy plays an important role in shaping adolescents' confidence to carry out prevention. The comprehensive sexual education model is one of the educational approaches that can increase adolescents' self-efficacy through providing information and strengthening prevention skills. This study aims to determine the effect of the comprehensive sexual education model on the self-efficacy of sexual violence prevention in adolescents at SMAN X Suwawa. The study used a quantitative approach with a pre-experimental one-group pretest-posttest design and involved 61 respondents selected through cluster random sampling technique. The research instrument is in the form of a questionnaire in the form of a dichotomy question. The results showed that most adolescents experienced excellent self-efficacy (91.8%), while the rate of self-efficacy was good (8.2%) after being given intervention. The results of the Wilcoxon signed rank test showed a p-value = 0.006 (< 0.05), which indicates that there is a significant influence of the comprehensive sexual education model on the self-efficacy of preventing sexual violence in adolescents at SMAN X Suwawa. Schools are advised to integrate comprehensive sexuality education in learning activities and counseling guidance services.